Human Properdin Modulates Macrophage: Mycobacterium bovis BCG Interaction via Thrombospondin Repeats 4 and 5 - Al-Mozaini, Maha Ahmed; Tsolaki, Anthony G.; Abdul-Aziz, Munirah; Abozaid, Suhair M.; Al-Ahdal, Mohammed N.; Pathan, Ansar A.; Murugaiah, Valarmathy; Makarov, Evgeny M.; Kaur, Anuvinder; Sim, Robert B.; Kishore, Uday; Kouser, Lubna (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis can proficiently enter macrophages and diminish complement activation on its cell surface. Within macrophages, the mycobacterium can suppress macrophage apoptosis and survive within the intracellular environment. Previously, we have shown that complement regulatory proteins such as factor H may interfere with pathogen–macrophage interactions during tuberculosis infection. In this study, we show that Mycobacterium bovis BCG binds properdin, an upregulator of the complement alternative pathway. TSR4+5, a recombinant form of thrombospondin repeats 4 and 5 of human properdin expressed in tandem, which is an inhibitor of the alternative pathway, was also able to bind to M. bovis BCG. Properdin and TSR4+5 were found to inhibit uptake of M. bovis BCG by THP-1 macrophage cells in a dose-dependent manner. Quantitative real-time PCR revealed elevated pro-inflammatory responses (TNF-α, IL-1β, and IL-6) in the presence of properdin or TSR4+5, which gradually decreased over 6 h. Correspondingly, anti-inflammatory responses (IL-10 and TGF-β) showed suppressed levels of expression in the presence of properdin, which gradually increased over 6 h. Multiplex cytokine array analysis also revealed that properdin and TSR4+5 significantly enhanced the pro-inflammatory response (TNF-α, IL-1β, and IL-1α) at 24 h, which declined at 48 h, whereas the anti-inflammatory response (IL-10) was suppressed. Our results suggest that properdin may interfere with mycobacterial entry into macrophages via TSR4 and TSR5, particularly during the initial stages of infection, thus affecting the extracellular survival of the pathogen. This study offers novel insights into the non-complement related functions of properdin during host–pathogen interactions in tuberculosis.